Inculcating spiritual intelligence to enhance students' psychological wellbeing - Anita, Abdul Rani; Haslinda, Hashim; Fatimah, Ali; Imaduddin, Abidin; Aini, Ahmad (Future Academy, 2017)
Students who have psychological problems in their lives may also have problems in their academic performance. Inculcating Spiritual Intelligence (SI) is believed to be able to overcome psychological problems (Piedment, 2001) such as depression, anxiety and stress. However, not every student has the inspiration and knowledge to enhance their own SI. At Universiti Malaysia Pahang (UMP), a module has been developed for this purpose. The UMP SI module focuses on Islamic values to enhance the role of 'Man as Caliph (leader)' and the connection between human and God. The objectives of this study are 1) to examine the effectiveness of the module on the students' emotional wellbeing and 2) to observe how it helps them to have more control of their lives. A qualitative research design was employed to collect data through interviews and reflections from 20 students who voluntarily participated in this study. Participants were required to apply the SI module in their daily lives for 40 days. They provided positive feedback especially after they had implemented the module. From the responses, there were positive changes in their behaviour especially when dealing with their emotions. The module was able to help them relieve stress, work better with others and become more focus in the classrooms. These findings revealed that the UMP SI Module is useful to university students and will also be beneficial for educators and counsellors to enhance students' psychological wellbeing.